2013
DOI: 10.1007/s11748-012-0194-0
|View full text |Cite
|
Sign up to set email alerts
|

A treatment strategy for early thrombosed Stanford type A acute aortic dissection

Abstract: Our strategy for the treatment of early thrombosed Stanford type A acute aortic dissection is reasonable, and the mid-term results were acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[ 5 ] suggests that patients with AIH in the form of intramural hematoma who exhibit increased values of CRP > 7.2 approximately 2 weeks after the onset of clinical symptoms are more susceptible to unfavorable events such as aortic dissection or rupture and should be treated with surgery. In a recently published study, Uzuka postulates an aggressive therapeutic approach for hemodynamically unstable patients and in cases in which the ascending aortic diameter is > 50 mm or the thickness of the hematoma is > 10 mm [ 8 , 9 ]. In the remaining cases, it is recommended to carefully monitor the patient's condition and repeat imaging examinations in order to detect possible disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] suggests that patients with AIH in the form of intramural hematoma who exhibit increased values of CRP > 7.2 approximately 2 weeks after the onset of clinical symptoms are more susceptible to unfavorable events such as aortic dissection or rupture and should be treated with surgery. In a recently published study, Uzuka postulates an aggressive therapeutic approach for hemodynamically unstable patients and in cases in which the ascending aortic diameter is > 50 mm or the thickness of the hematoma is > 10 mm [ 8 , 9 ]. In the remaining cases, it is recommended to carefully monitor the patient's condition and repeat imaging examinations in order to detect possible disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that type A IMH is more likely to progress, regardless of the diameter of the aorta, and, thus that prompt surgical repair should be performed (6,68). However, Uzuka et al (67) recommended that emergency or urgent surgery not be considered for a hemodynamically stable patient unless the diameter of the ascending aortic was ≥ 50 mm or the thickness of the thrombosed false lumen was ≥ 10 mm. The mortality rate for open surgical treatment of type A IMH was 0-42.9% in hospital and 0-27.1% during follow-up ( Table 2).…”
Section: Type Amentioning
confidence: 99%
“…For thrombosed type dissection of the ascending aorta best treatment remains debatable. Studies from Asia have recently shown medical treatment to be a reasonable alternative for this specific subgroup [4][5][6][7][8].…”
mentioning
confidence: 99%